A systematic review of the clinical evidence for an association between type I hypersensitivity and inner ear disorders - Zeng, Bin; Domarecka, Ewa; Kong, Lingyi; Olze, Heidi; Scheffel, Jörg; Moñino-Romero, Sherezade; Siebenhaar, Frank; Szczepek, Agnieszka J. (Frontiers in Neurology, 2024)
Inner ear disorders have a variety of causes, and many factors can contribute to the exacerbation of cochlear and vestibular pathology. This systematic review aimed to analyze clinical data on the coexistence and potential causal interaction between allergic diseases and inner ear conditions. A search of PubMed and Web of Science identified 724 articles, of which 21 were selected for full-text analysis based on inclusion and exclusion criteria. The epidemiologic evidence found overwhelmingly supports an association between allergic disease and particular inner ear disorders represented by a high prevalence of allergic reactions in some patients with Ménière’s disease (MD), idiopathic sudden sensorineural hearing loss (ISSHL), and acute low-tone hearing loss (ALHL). In addition, patients with MD, ISSHL, and ALHL had higher levels of total serum IgE than healthy subjects. Finally, in some cases, changes in cochlear potential may have been induced by antigen exposure, while desensitization alleviated allergy and inner ear-related symptoms. The exact mechanism of interaction between the auditory/vestibular and immune systems is not fully understood, and further clinical and basic research is needed to understand the relationship between the two systems fully.